Decomposição da diferença nos resultados do PISA: uma comparação do Brasil com os países da OCDE - Lima, Abílio Francisco de (2019)
This work analyses the difference in educational performance of students among Brazil and OECD in the subject areas of Reading and Mathematics based on the PISA exams of 2009, 2012 and 2015. From the educational production function for scores of Brazil, the work shows that the Family background positively affects students' achievement in the Reading and Math exams. In the 2015 exam, the performance differential in favor of OECD students was 57.17 points in the Reading test and 74.80 points in the Mathematics test, showing a downward trajectory compared to 2009 and 2012. However, the differential due to the dotations of the students showed a growth trend over the observed period. The results of the decomposition of differences also indicate that the repetition rate, family socioeconomic conditions, and school environment also contribute to the observed difference between the academic performance of OECD and Brazilian students.